2015
DOI: 10.1016/j.neuron.2014.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Filtering of Visual Information by Neuronal Ensembles in the Primate Lateral Prefrontal Cortex

Abstract: The activity of neurons in the primate lateral prefrontal cortex (LPFC) is strongly modulated by visual attention. Such a modulation has mostly been documented by averaging the activity of independently recorded neurons over repeated experimental trials. However, in realistic settings, ensembles of simultaneously active LPFC neurons must generate attentional signals on a single-trial basis, despite the individual and correlated variability of neuronal responses. Whether, under these circumstances, the LPFC can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
116
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(124 citation statements)
references
References 94 publications
7
116
1
Order By: Relevance
“…Reports of the effects of ensemble r sc structure on information content vary significantly in sign and magnitude (19,22,24,27,42,48,49); our results can help reconcile these disparate accounts. For example, previous studies that applied decoding techniques to simultaneously recorded ensembles found that removing the r sc structure decreased decoding accuracy for grating orientation (48) and remembered location (49) whereas another study reported a positive effect of pairwise r sc on information coding (32).…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…Reports of the effects of ensemble r sc structure on information content vary significantly in sign and magnitude (19,22,24,27,42,48,49); our results can help reconcile these disparate accounts. For example, previous studies that applied decoding techniques to simultaneously recorded ensembles found that removing the r sc structure decreased decoding accuracy for grating orientation (48) and remembered location (49) whereas another study reported a positive effect of pairwise r sc on information coding (32).…”
Section: Discussionmentioning
confidence: 53%
“…We collected spike data from a total of 545 single units and multiunits across 12 recording sessions, out of which 417 (76%) exhibited sustained activity and selectivity during the delay epoch (P < 0.05, Kruskal-Wallis; firing rate × location) (Materials and Methods). We included both multiunits and single units in our analyses, as in similar previous studies (21,25,27,34). A unit's preferred location during a given epoch was defined as the location that elicited the largest response averaged over that epoch ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations